What did I get Wrong? Supporting the Feedback Process in Computer Science Education - Falcão, Taciana Pontual; Arêdes, Verenna; Wagner, Samuel Souza; Uchoa, João Pedro Cavalcanti; Luisi, Victoria; Mello, Rafael Ferreira (Anais do Workshop sobre Educação em Computação (WEI); 2022: Anais do XXX Workshop sobre Educação em ComputaçãoDO - 10.5753/wei.2022.223150, 2022)
In learning processes, feedback given to students by instructors is essential to guide students and help them improve from their mistakes. However, in higher education, instructors feel unable to give quality and timely feedback due to work overload and lack of time. As online classes became common due to the Covid 19 pandemic, and with increasing numbers of students per class, giving feedback beyond grades became even less realistic. We interviewed Computer Science instructors and students to investigate the specific difficulties and barriers related to giving and receiving feedback. We present the findings derived from qualitative analysis of the interviews and propose Tutoria, a platform designed to support a better feedback experience for all.